PENGARUH MEDIA WORDWALL TERHADAP PARTISIPASI BELAJAR PENDIDIKAN AGAMA KATOLIK SISWA KELAS V SDK KRISTUS RAJA SURABAYA - Peka, Patrisia Somi; Permana, Natalis Sukma (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
Student participation in the learning process can be influenced by learning media. Wordwall, as an interactive game-based learning, is considered capable of enhancing students' participation. This research aims to determine the influence of Wordwall media on the learning participation of grade V Catholic Religious Education students at Kristus Raja Catholic Elementary School, Surabaya. This study uses a pre-experimental method with a one-shot case study design. The population consists of grade V Catholic Religious Education students. The questionnaire's validity is tested using corrected item-total correlation, while reliability is measured with Cronbach Alpha. Data collection employs questionnaires and tests, analyzed using descriptive statistics and the Wilcoxon test using SPSS version 29. The results of the study indicate a positive influence of Wordwall media on students' learning participation. This is evident from the questionnaire scores, which increase from moderate to high levels, and a significance value of 0.002 smaller than 0.05, leading to the valid hypothesis. Based on the result of the study, it can be concluded that using Wordwall media enhances the learning participation of grade V Catholic Religious Education students at Kristus Raja Catholic Elementary School, Surabaya.